Study on Stochastic Quasi-Linear Partial Differential Equations of Evolution - Anguraj, A.; Ramkumar, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, the existence and uniqueness of local mild solution of a stochastic counterpart of Tosio Kato’s Quasi-linear partial differential equation with additive cylindrical wiener process in a separable Hilbert space is established using contraction mapping principle.